Urgensi Etika Pejabat Publik dan Peranan Generasi Z dalam Studi Administrasi Publik - Yogi Oktari (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2023)
This paper aims to explore how the phenomenon of demoralizations and ethical dysfunction in the realm of public administration has developed massively, so there is a risk of creating a wave of public distrust. It’s necessary to have a critical study of public ethics, along with the transformation of service ethics assessment standards in accordance with the time and paradigms. This study used library research with data collection technique is carried out by reviewing scientific journals that are considered relevant to this study. The results of this study indicate that there are two types of ethical violations that are mostly done by public official in Indonesia, namely abuse of power and maladministration. Factors causing the proliferation of ethical violations in Indonesia are weak law enforcement and public permissiveness towards unethical behavior. The active role of Generation Z is needed to maintain a healthy democratic climate and reduce public permissiveness toward various forms of ethical violations.